How Enaction and Ecological Approaches Can Contribute to Sports and Skill Learning - Avilés, Carlos; Navia, José A.; Ruiz-Pérez, Luis-Miguel; Zapatero-Ayuso, Jorge A. (Frontiers in Psychology, 2020)
The purpose of this paper is to explain learning in sports and physical education (PE) from the perspective of enactive and ecological psychology. The learning process is first presented from the enactive perspective, and some relevant notions such as sense-making and sensorimotor schemes are developed. Then, natural learning environments are described, and their importance in the human development process is explained. This is followed by a section devoted to the learner’s experience in which some research methods are explained, such as neurophenomenology, in addition to self-confrontation, interviews aimed at bringing out the meaning, sensations, and emotions that performers experience when they are immersed in their sport or a PE class. The sections on the ecological approach deal with the attunement, calibration, the education of intention, and the importance of representative experimental designs. The last section addresses the main similarities and differences between the two approaches. Finally, we state our theoretical position in favor of a common project that brings together the main elements of both post-cognitive approaches.